Effect of cementation technique and types of resin cements on the shear bond strength of the indirect composite "inlay" - Garcia, Ma. Rossabele N.
Introduction: Two types of cementation techniques are used to cement tooth colored indirect restorations, the conventional method or the delayed dentin seal (DDS) and the resin impregnation or the immediate dentin seal (IDS). With the conventional method (DDS), the dentinal tubules are sealed prior to final cementation. It has been reported that immediately sealing the dentinal tubules after tooth preparation (IDS) produces higher shear bond strengths as compared to the conventional method. The purpose of this study are: 1) to compare the effect of immediate dentin sealing and conventional dentin sealing on the shear bond strength of indirect restorations cemented with resin cements and 2) to determine which type of resin cement produces the highest bond strength with immediate dentin sealing and delayed dentin sealing.